The effect of racemic gossypol and AT-101 on angiogenic profile of OVCAR-3 cells: a preliminary molecular framework for gossypol enantiomers - Varol, U.; Karaca, B.; Tunali, D.; Degirmenci, M.; Cirak, Y.; Purcu, D.U.; Uzunoglu, S.; Sezgin, C.; Karabulut, B.; Sanli, U.A.; Uslu, R. (Experimental Oncology, 2009)
To compare the effect of racemic gossypol with its (–)/(–) enantiomer (AT-101) on expression profiles of angiogenic molecules by mRNA levels in human ovarian cancer cell line OVCAR-3. Methods: Cell viability assay (2,3-bis (2-methoxy-4-nitro-5- sulfophenyl)-5-[(phenylamino) carbonyl]-2H-tetrazolium hydroxide) was used to detect cytotoxicity of gossypol enantiomers. DNA fragmentation by an enzyme-linked immunosorbent (ELISA) assay was used to evaluate the rate of apoptosis. The mRNA expression levels of angiogenic molecules were investigated by Human Angiogenesis RT2 ProfilerTM PCR Array (SuperArray, Frederick, MD). Results: Both racemic form and AT-101 resulted in a significant cytotoxicity and induced apoptosis. This effect was observed in a dose- and time dependent manner. However, AT-101 was much more potent. In addition, the treatment of 10 μM of racemic gossypol alone and 3 μM of AT-101 alone resulted in significant down-regulation (≥ 3 fold) in mRNA levels of some pivotal angiogenic molecules in OVCAR-3, but altered gene profiles were different by the treatment of each enantiomer. Conclusion: The efficacy of two gossypol enantiomers in OVCAR-3 cells showed distinction. AT-101 was much more potent than racemic gossypol, not only by means of cell death and apoptosis, but also by modulation of angiogenic molecules released from OVCAR-3 cells. Further studies with endothelial cells should be done to verify the anti-angiogenic effect of gossypol enantiomers in cancer treatment.